Spatial variations of leaf morphometry in mangroves in La Havana, Cuba - Denis, Dennis (Universidad de Costa Rica, 2020)
Introduction: Mangroves represent 11 % of the emerged land of Cuba. There is no previous research describing foliar characteristics, but these variables can be used as health indicators in forest ecosystems. Objective: In the current study we describe folial morphometry in four mangroves around Havana city: Bajos de Santa Ana, Cojímar, Rincón de Guanabo and El Cobre – Itabo lagoon. Methods: We collected 1 472 leaves´ samples of Rhizophora mangle, Avicennia germinans and Laguncularia racemosa, between April and July in 2019, to extract eight foliar variables: length, width, area, perimeter, lateral asymmetry, inner angles and shape index. Results: Geographic differences several variables of leaves in R. mangle and A. germinans were detected, but L. racemosa showed high similarity among localities. Differences can be explained by environmental differences in localities. Conclusions: There is a need for more extensive research on these kinds of foliar indicators to support it use in future monitoring or researches, and for that using digital pictures fotografías pose many advantages.